2019
DOI: 10.1002/jgh3.12172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gluten‐free diet and compliance on quality of life in pediatric celiac disease patients

Abstract: Background Quality of life (QOL) in children with celiac disease (CD) has been sparsely studied. Aims We aimed to study QOL in pediatric CD and the effect of a gluten‐free diet (GFD) in a North Indian population. Methods QOL was assessed at baseline and 6 months after GFD using a pediatric symptom checklist (PSC) score. The effect of GFD was assessed using a CD‐specific questionnaire on domains such as dietary compliance, parental behavior and perceptions, children's feeling, and difficulty identifying gluten‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…In relation, risk of cognitive, emotional, and behavioral difficulties were higher in children and adolescents with newly diagnosed CD than those in remission after GFD commencement (51). Two studies found that risk of psychosocial problems reduced after 6 months (4) and 1 year of a GFD (17). It is not clear from these findings whether this is due to time, or the process of psychological adjustment (ie, developing adaptive coping patterns and reducing negative illness identity).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In relation, risk of cognitive, emotional, and behavioral difficulties were higher in children and adolescents with newly diagnosed CD than those in remission after GFD commencement (51). Two studies found that risk of psychosocial problems reduced after 6 months (4) and 1 year of a GFD (17). It is not clear from these findings whether this is due to time, or the process of psychological adjustment (ie, developing adaptive coping patterns and reducing negative illness identity).…”
Section: Resultsmentioning
confidence: 99%
“…Recent advances in food labeling and new policies, mostly in Western regions including the European Union and the United Kingdom (4,8), may increase awareness and assurance of GF foods to facilitate everyday life (55). It is reported there remains a need for stricter food labeling policies in Asia and the Indian subcontinent (4). While the advances in policy could suggest better psychosocial well-being in Western countries, this is inconsistent with our results comparing CDDUX scores between regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ubiquitous nature of gluten constitutes a global problem for coeliacs because the GFD restricts the choice of many foods, with a significant impact on the behavioral, emotional, and psychosocial domains of coeliacs ( 7 , 30 ). Assessing the HRQoL has been increasingly acknowledged in research and clinical studies in CD, thus, contributing to improved interventions and measures that can reduce the burden on the affected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zenbait ikerkuntzetan baieztatu da osasun hezkuntza garatzea eta pertsona zeliakoei eskaintzea beharrezkoa dela euren egoera sozialari aurre egiteko Chellan et al, 2019). Horregatik guztiagatik, Nutrizio Hezkuntza programak osasun fisikoa eta soziala bilatu behar ditu.…”
Section: Ikergazte 2021unclassified